Преступление и наказание: [роман] / Фёдор Достоевский - Достоевский Федор Михайлович (Бест прайс, 2023)
Экземпляры: ф.23 (20230802) / Инвентарный номер: 63810 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Д 70 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44